PENGAWASAN CAMAT DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI KECAMATAN MANDOLANG KABUPATEN MINAHASA - RATU, RENDI LODWEYK; LENGKONG, FLORENCE; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to determine the supervision of the Sub-District Head in the administrationof village governance in the Mandolang District of Minahasa Regency. This study uses a descriptivequalitativeapproach. The research informants were the Mandolang Sub-District Head, MandolangDistrict Government Section Head, two Village Heads, two BPD chairmen, and two LPM chairmen; atotal of 10 informants. Data collection uses interview guidelines, while the analytical technique used is theanalysis of interactive models from Miles and Huberman. Based on the results of data analysis,conclusions were drawn: (1) Direct Sub-District Head oversight of village administration is carried outwell through observation, observation or direct examination of the village carried out by the Sub-DistrictHead alone or through the assignment of subordinates; (2) Sub-district Head indirect supervision iscarried out by requesting periodic written reports (every month, quarterly, and every six months)regarding village administration, and village government performance reports at the end of the fiscalyear. Indirect supervision also requests oral and explanatory reports to the village head at the sub-districtcoordination / evaluation of sub-district. Based on this research it is recommended: (1)The Sub-DistrictHead should go down to villages more often to monitor, observe or directly check the running of villageadministration. (2) The Sub-District Head should check / verify the truth of the written report by visitingthe village and having a dialogue with the BPD, LPM, and local village community leaders.Keywords: Supervision, Sub-District Head, Village Government.